1988
DOI: 10.1227/00006123-198802000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Indications for Treatment and Classification of 132 Carotid-Cavernous Fistulas

Abstract: Classification of carotid-cavernous fistulas (CCFs) into the four types described by Barrow allows the surgeon to choose the optimal therapy for each patient. Type A patients have fast flow fistulas that are manifest by a direct connection between the internal carotid arterial siphon and the cavernous sinus through a single tear in the arterial wall. The best therapy is obliteration of the connection by a detachable balloon. Ninety-two of 95 traumatic CCFs were treated in this fashion. Direct surgical exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
126
1
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(134 citation statements)
references
References 0 publications
2
126
1
5
Order By: Relevance
“…Higashida et al 1 reported preservation of the parent ICA in 88% of patients with DCCFs treated by using detachable balloons, while other authors have described a need for parent artery occlusion in as many as 20% of cases. 2,3 In addition, straying, overinflation, or migration of a detached balloon may lead to deterioration of ocular palsy. 4 GDCs were previously used in cases in which the balloon technique failed.…”
mentioning
confidence: 99%
“…Higashida et al 1 reported preservation of the parent ICA in 88% of patients with DCCFs treated by using detachable balloons, while other authors have described a need for parent artery occlusion in as many as 20% of cases. 2,3 In addition, straying, overinflation, or migration of a detached balloon may lead to deterioration of ocular palsy. 4 GDCs were previously used in cases in which the balloon technique failed.…”
mentioning
confidence: 99%
“…Higashida et al [15] reported preservation of the parent artery in 88% of patients with TCCFs treated by using detachable balloons; other authors have described a need for parent artery occlusion in as many as 20% of cases [16,17].…”
Section: Review Of Endovascular Management Of Traumatic Carotid-cavermentioning
confidence: 99%
“…DAVMs have been reported to occur in patients with various systemic conditions, particularly syndromes characterised by connective tissue disorders. Potential associations include: atypical Sturge-Weber related syndrome [114], blue rubber-bleb nevus syndrome [115], congenital toxoplasmosis [116], Ehlers-Danlos syndrome [117][118][119], fibromuscular dysplasia [117,120,121], hereditary hemorrhagic telangiectasia [122,123], Marfan's syndrome [124], osteogenesis imperfecta [117], polyarteritis nodosa [125], pseudoxanthoma elasticum [126], Rendu-Osler-Weber syndrome [127], syndactyly [128], and von Recklinghausen's disease [129].…”
Section: Geneticsmentioning
confidence: 99%